Lipoic Acid Restores Binding of Zinc Ions to Human Serum Albumin - Al-Harthi, Samah; Chandra, Kousik; Jaremko, Łukasz (Frontiers in Chemistry, 2022)
Human serum albumin (HSA) is the main zinc zinc(II) carrier in blood plasma. The HSA site with the strongest affinity for zinc(II), multi-metal binding site A, is disrupted by the presence of fatty acids (FAs). Therefore, the FA concentration in the blood influences zinc distribution, which may affect both normal physiological processes and a range of diseases. Based on the current knowledge of HSA's structure and its coordination chemistry with zinc(II), we investigated zinc interactions and the effect of various FAs, including lipoic acid (LA), on the protein structure, stability, and zinc(II) binding. We combined NMR experiments and isothermal titration calorimetry to examine zinc(II) binding to HSA at a sub-atomic level in a quantitative manner as well as the effect of FAs. Free HSA results indicate the existence of one high-affinity zinc(II) binding site and multiple low-affinity sites. Upon the binding of FAs to HSA, we observed a range of behaviors in terms of zinc(II) affinity, depending on the type of FA. With FAs that disrupt zinc binding, the addition of LA restores HSA's affinity for zinc ions to the levels seen with free defatted HSA, indicating the possible mechanism of LA, which is effective in the treatment of diabetes and cardiovascular diseases.